Vegetation and Community Structure of Mangrove in Bama Resort Baluran National Park Situbondo East Java - Hariyanto, Sucipto; Fahmi, Akhmad Kharish; Soedarti, Thin; Suwarni, Emy Endah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Ecotourism development program at Bama beaches area require baseline data of mangrove structure at Bama Resort and in the past two decades has been lost about 35% area of mangrove forest in Indonesia and in the worldThe aims of this study was to find structure, composition, distribution and zonation patterns of mangroves at Bama Resort Baluran Nasional Park. Ten belt-transects were laid perpendicular to the shoreline, using standard methods. Vegetation structure was determined using data collected on plant species diversity, density, basal area, and the number of each species of mangroves. Shannon Wiener index to calculated diversity, evennes and Simpson to calculated dominance index. The results show there are 2 families and 6 mangrove species occurring in the study areas that is Rhizophoraceae (Rhizophora stylosa, Rhizophora mucronata, Rhizophora apiculata, Bruguiera gymnorrhiza, and Ceriops tagal) and Araceae (Nypa fruticans). The highest importance value was R. apiculata (229.90%) for trees, R. apiculata (148.69%) for the sapling, and R. apiculata (244.83%) for the seedling. The diversity (H) and dominance index (C) values were moderate (1.79) and 0.521. The most dominant species was R. apiculata (C=0.487). The mangrove zonation pattern from coastline to the mainland was R. stylosa, R. mucronata, and R. apiculata, in the outer zone, respectively (zone directly adjacent to the sea); B. gymnorrhiza and C. tagal in the middle zone; and N. fruticans in the zone that adjacent to the mainland. The present study will aid in the conduct and preservation planning of mangrove forest especially at Bama coast and generally in the coastal areas of Indonesia.